Blockade of Melatonin Receptors Abolishes Its Antiarrhythmic Effect and Slows Ventricular Conduction in Rat Hearts - Durkina, Aleksandra V; Szeiffova Bacova, Barbara; Bernikova, Olesya G; Gonotkov, Mikhail A; Sedova, Ksenia A; Cuprova, Julie; Vaykshnorayte, Marina A; Diez, Emiliano R; Prado, Natalia J; Azarov, Jan E (International journal of molecular sciences, 2023)
Melatonin has been reported to cause myocardial electrophysiological changes and prevent ventricular tachycardia or fibrillation (VT/VF) in ischemia and reperfusion. We sought to identify electrophysiological targets responsible for the melatonin antiarrhythmic action and to explore whether melatonin receptor-dependent pathways or its antioxidative properties are essential for these effects. Ischemia was induced in anesthetized rats given a placebo, melatonin, and/or luzindole (MT1/MT2 melatonin receptor blocker), and epicardial mapping with reperfusion VT/VFs assessment was performed. The oxidative stress assessment and Western blotting analysis were performed in the explanted hearts. Transmembrane potentials and ionic currents were recorded in cardiomyocytes with melatonin and/or luzindole application. Melatonin reduced reperfusion VT/VF incidence associated with local activation time in logistic regression analysis. Melatonin prevented ischemia-related conduction slowing and did not change the total connexin43 (Cx43) level or oxidative stress markers, but it increased the content of a phosphorylated Cx43 variant (P-Cx43368). Luzindole abolished the melatonin antiarrhythmic effect, slowed conduction, decreased total Cx43, protein kinase Cε and P-Cx43368 levels, and the IK1 current, and caused resting membrane potential (RMP) depolarization. Neither melatonin nor luzindole modified INa current. Thus, the antiarrhythmic effect of melatonin was mediated by the receptor-dependent enhancement of impulse conduction, which was associated with Cx43 phosphorylation and maintaining the RMP level.
Keywords: sodium current; potassium current; conduction velocity; melatoninové receptory; srdeční arytmie; melatonin; Arrhythmias, Cardiac; Melatonin; krysa rodu Rattus; kardiomyocyty; Animals; connexin-43; zvířata; Anti-Arrhythmia Agents; Rats; Myocytes, Cardiac; Receptors, Melatonin; konexin 43; Connexin 43; post-ischemic arrhythmias; rat heart; antiarytmika